Late Onset Corneal Haze Post Photorefractive Keratectomy - Agnia, Emeralda Brilian; Kriskasari, Georgina Tara; Dharmawidiarini, Dini; Napitupulu, Sahata P. H. (Universitas Airlangga, 2024)
Introduction: Photorefractive keratectomy (PRK) is a surface ablation procedure to correct refractive errors. Regardless of the safety and efficacy, corneal haze may occur after PRK, and it remains one of the most feared complications because it can impair good visual outcomes. Case Presentation: A 20-year-old woman complained of blurred vision in her right eye (RE) after undergoing PRK elsewhere six months before admission with a history of refraction of S-12.75 C-1.75 x 10° preoperatively and S-0.75 postoperatively. Six-month postoperative uncorrected visual acuity (UCVA) was 0.01, best corrected visual acuity (BCVA) was 0.5 with S-7.00 C-0.75 x 50°. A slit lamp examination revealed grade three corneal haze. Anterior optical coherence tomography (OCT) showed the hyperreflective area with 132 μm deep into the stroma. The patient underwent phototherapeutic keratectomy (PTK) and mitomycin-C (MMC) treatment to a depth of 50 μm Ø6.5mm transition zone 0.5 mm. Two months later, UCVA was 0.2, BCVA was 0.63 with S-2.50 C-0.50 x 90°, and slit lamp examination revealed no haze remaining. Conclusions: This case illustrates the potential risk for corneal haze development, mainly when PRK is performed at greater treatment depths. However, with phototherapeutic keratectomy and mitomycin-C treatment, an excellent visual outcome and vision restoration can be obtained.